Advancing AI in Higher Education: Responsible Practices, Leader's Cognitive Involvement, and Adoption Synergy (International Journal of Food and Nutritional Sciences, 2022)
The rapid growth of artificial intelligence (AI) is reshaping higher education. This study examines AI's potential in Indian universities, considering stakeholder views and leadership roles. Key questions explored include how responsible AI affects AI adoption and the role of leadership cognitive engagement. It is a quantitative research, and after running CFA using AMOS, SPSS was utilised for mediation analysis. The study concludes that responsible AI practices and leadership engagement are crucial for effective AI adoption. AI's role in education's future hinges on ethical practices and proactive leadership. Recognising the mediating role of the leader's cognitive engagement highlights the need of leadership development courses that increase leaders' knowledge of responsible AI and its implications. Such courses/ training can prepare top management of these HEIs to advocate for the use of AI technology while keeping ethical considerations in mind.